Genomic epidemiology of carbapenem- and/or colistin-resistant Pseudomonas aeruginosa in the Gauteng region, South Africa - Kock, Martha Magdalena (University of Pretoria, 2022)
Thesis (PhD (Medical Microbiology))--University of Pretoria, 2021.